How British is English: Culture and Contemporary Language Learning - Vera Ošmjanski (Etnoantropološki Problemi, 2024)
The paper examines the extent to which it is possible to displace English as a functional communication tool from its culturally rich British contexts and associations. Starting from the analysis of the relationship between culture and language, the study discusses the ties between British culture and English in the context of its emergence as a global means of communication. In addition, the paper refers to developments in language pedagogy to outline the role of British culture in contemporary English learning. The conclusion is that reducing English to a mere culturally neutral container for information is not beneficial for educational outcomes, as outlined in the two principal reference documents for foreign language learning, the CEFR and ACTFL. A joint literacy in English and its culture will not foster undesirable individual acculturation but contribute to the development of intercultural competence among learners from diverse backgrounds who bring their own negotiations with British culture.